PERILAKU SOSIAL MASYARAKAT HINDU DALAM PENEGAKAN KEGIATAN BANJAR ADAT DI DESA SIDOREJO KECAMATAN TAMBAN CATUR KABUPATEN KAPUAS - I Made Kastama (Belom Bahadat, 2020)
Abstract The purpose of this research was to explain the social behavior of Hindu community in the midst of Banjar Adat’s life. Community life between members of the community and its social groups affects each other. Members of the community are required to live peacefully together with the development of the times that are coupled with social changes as a result of modernization. Social norms and legal norms are expected to accompany the current development in the pattern of community relations. Social action theory was used to analyse the social behavior of the community with its attention on goal-oriented action and the motivation of the subject. Systems theory was used to analyse that life was a system, both in the context of micro (microcosm/ human) and macro (macrocosm/ the universe). Qualitative methods were used to reveal and understand something behind the phenomenon that occured. Social behavior of the community was held on the activities of Banjar Adat with Hindu community activities conducted by social interaction in the form of mutual assistance and cooperation which was also influenced by the rules imposed such as customary rules that people often knew with the name Awig-Awig to maintain the balance of human life both among human beings, between society and with natural environment. Every social behaviour of community members affected the social interaction of Banjar Adat. The pattern of relationship in the community was conducted based on mutual agreement that contained in the Awig-Awig norm.